Togo - Blake, Robert J. (New York : Philomel Books, 2002)
In 1925, Togo, a Siberian husky who loves being a sled dog, leads a team that rushes to bring diphtheria antitoxin from Anchorage to Nome, Alaska.
Keywords: Sled dogs -- Fiction; Siberian husky -- Fiction; Dogs -- Fiction; Diphtheria -- Fiction; Alaska -- Fiction